1996
DOI: 10.1042/bj3170447
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and optical properties of copper-substituted alcohol dehydrogenase: a bisthiolate copper (II) complex

Abstract: Replacement of the catalytic Zn(II) in horse liver alcohol dehydrogenase (HLADH) with copper produces a mononuclear Cu(II) chromophore with a ligand set consisting of two cysteine sulphurs, one histidine nitrogen plus one further atom. The fourth ligand to the metal ion and the conformation of the protein may be altered by addition of exogenous ligands and/or the cofactor NADH. Absorbance, CD, low-temperature magnetic CD (MCD) and EPR spectra are presented of copper-substituted HLADH samples in both 'open' and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 33 publications
0
15
2
Order By: Relevance
“…Such a site was available in horse liver alcohol dehydrogenase from which the natural metal in the catalytic site, Zn, had been removed and replaced by Cu. This site did not show the strong MCD features at 480 and 520 nm typical of all Cu, sites [54]. Note also that the Chan model contradicts the results from the study on the linear electric field effect by Mims et al 1491.…”
Section: Progress Through Advances In Related Fields Protein Chem-contrasting
confidence: 52%
See 1 more Smart Citation
“…Such a site was available in horse liver alcohol dehydrogenase from which the natural metal in the catalytic site, Zn, had been removed and replaced by Cu. This site did not show the strong MCD features at 480 and 520 nm typical of all Cu, sites [54]. Note also that the Chan model contradicts the results from the study on the linear electric field effect by Mims et al 1491.…”
Section: Progress Through Advances In Related Fields Protein Chem-contrasting
confidence: 52%
“…In 1980, Mims et al [49] concluded from spin-echo studies and from the observation of the linear electric field effect in spin-echo EPR that 'The results indicate that the symmetry is not tetrahedral and that the ligation pattern is unlike that for either type 1 or type 2 Cu in other Cu proteins.' In order to obtain more definitive information on the ligands of Cu,, Chan, Scholes and their associates [50] purified COX from yeast auxotrophs, which had been supplemented with [1,3- [54]. Note also that the Chan model contradicts the results from the study on the linear electric field effect by Mims et al 1491.…”
Section: Progress Through Advances In Related Fields Protein Chem-contrasting
confidence: 42%
“…The electronic absorption data of the Glu114XCu A Az variants indicate two sharp peaks in the 410–600 nm region and a broad feature at ~700–800 nm, similar to the pyrazole-substituted HLADH, which displays two peaks at ~400–500 nm, and a broad feature ~600–800 nm. 6062 The EPR results indicate the presence of mononuclear T2Cu species with thiolate ligands. In all the variants, the EPR data suggest two mononuclear Cu complexes with minor differences in ligand coordination/geometry.…”
Section: Resultsmentioning
confidence: 99%
“…Although both the g z and A z values are higher than the I x2 of Glu114GlyCu A Az, these parameters are similar to the Cu(Cys) 2 (His)L (L=pyrazole, NADH) complex of HLADH ( g z =2.200, A z =115 × 10 −4 cm −1 ). 6062 Based on this similarity, we assign the I x2 of Glu114GlnCu A Az as having a similar Cu(Cys) 2 (His)L (L=weak axial ligand) ligation/geometry.…”
Section: Resultsmentioning
confidence: 99%
“…The fifth and sixth positions are probably filled by water molecules coordinated through their oxygen atoms [18,19]. For the cysteinate-containing material the values of the above parameters indicate N amino N amino S thiolate S thiolate tetragonally-shaped coordination environment [20,21] with two molecules of water coordinated through their oxygen atoms in the fifth and sixth position.…”
Section: Characterization Of the Intercalated Complexesmentioning
confidence: 98%